SEKURITISASI ASET DALAM KONTRAK INVESTASI KOLEKTIF BERAGUN ASET DI INDONESIA - Paripurna P. Sugarda (Fakultas Hukum Universitas Gadjah Mada, 2008)
EBA is one of alternatif of financing for business world and investment instrument for investor. Yet, until nowdays, no company issued EBA in Indonesia capital market even though there have been quite number of Indonesia that companies that become originator of foreign securitization. Unvalailability of EBA in Indonesia capital market is because of the lack of knowledge of capital market participants in understanding EBA. The capital participant still consider that existing rule and regulation are in insuffient for the EBA to take place.